'I'm always walking on eggshells, and there's no chance of me ever being free': The mental health implications of Imprisonment for Public Protection in the community and post‐recall. (13th November 2020) - Harris, Mia; Edgar, Kimmett; Webster, Russell
Abstract: Background: Despite its abolition in 2012, the indeterminate sentence of Imprisonment for Public Protection (IPP) still casts a long shadow over the justice system. Recall is a growing problem: In June 2020, there were 1, 359 recalled IPP prisoners. Research documents the negative mental health implications of initial imprisonment under an IPP sentence; however, little is known about experiences on licence, or post‐recall. Aims: To explain how recalled IPP prisoners perceive being on licence, and in prison post‐recall, to affect their mental wellbeing. Methods: We draw on 31 interviews with recalled IPP prisoners, conducted for a wider project exploring the high rates of IPP recall. Results: Three themes emerged: a perpetual state of anxiety about recall and spending additional years behind bars; self‐imposed social isolation, both in the community and in prison; and a profound sense of hopelessness. People often feel trapped in an unjust and inevitable cycle of imprisonment, with little faith in a positive future. Conclusions: The government must make structural changes to stop the revolving door of IPP recall. In the short term, confidential mental health support should be available to people serving IPPs in prison and the community.